Antifungal activity of carvacrol and antifungal agent combinations against non-albicans Candida species - Nóbrega, Jefferson Rodrigues; Sousa, Paula Mariane Silva; Mota, Kelly Samara de Lira; Cordeiro, Laísa Vilar; Andrade Júnior, Francisco Patricio de; Oliveira, Wylly Araújo de (Scientia Plena, 2019)
The aim of this study was to determine the minimum inhibitory concentration of carvacrol and to evaluate the antifungal activity of carvacrol when combinated with fluconazole, ketoconazole or amphotericin B against non-albicans Candida species. MICs were determined using microdilution method, and the combination study was conducted using the checkerboard method. The carvacrol MIC ranged between 128 and 512 μg/mL. The greatest antifungal activity was displayed with ketoconazole. Conversely, fluconazole displayed the lowest activity. Amphotericin B showed MICs ranging from 0.5 to 2 μg/mL. The best combinations were observed against Candida guilliermondii and Candida parapsilosis, which presented synergistic efects. Additive efect was observed in three combinations, whereas, indifferent interactions were seen in six combinations. No antagonistic effects were observed. Based on these results, we conclude that carvacrol retains high activity against non-albicans Candida strains, and the combinations between carvacrol and the antifungals tested yielded significant effects.